Medical Informatics in Medical Research - Olola, C. H. O.; on Behalf of the SMAC Network; Missinou, M. A.; Issifou, S.; Anane-Sarpong, E.; Abubakar, I.; Gandi, J. N.; Chagomerana, M.; Pinder, M.; Agbenyega, T.; Kremsner, P. G.; Newton, C. R. J. C.; Wypij, D.; Taylor, T. E. (Methods of Information in Medicine, 2006)
Objectives: Computers are widely used for data management in clinical trials in the developed coutries, unlike in developing countries. Dependable systems are vital for data management, and medical decision making in clinical research. Monitoring and evaluation of data management is critical.In this paper we describe database structures and procedures of systems used to implement, coordinate, and sustain data management in Africa. We outline major lessons, challenges and successes achieved, and recommendations to improve medical informatics application in biomedical research in sub-Saharan Africa.Methods: A consortium of experienced research units at five sites in Africa in studying children with disease formed a new clinical trials network, Severe Malaria in African Children. In December 2000, the network introduced an observational study involving these hospital-based sites. After prototyping, relational database management systems were implemented for data entry and verification, data submission and quality assurance monitoring.Results: Between 2000 and 2005, 25,858 patients were enrolled. Failure to meet data submission deadline and data entry errors correlated positively (correlation coefficient, r = 0.82), with more errors occurring when data was submitted late. Data submission lateness correlated inversely with hospital admissions (r = –0.62).Conclusions: Developing and sustaining dependable DBMS, ongoing modifications to optimize data management is crucial for clinical studies. Monitoring and communication systems are vital in multi-center networks for good data management. Data timeliness is associated with data quality and hospital admissions.
Keywords: Medical informatics computing; malaria; multi-center studies